Antimicrobial resistance, virulence gene profiles, and molecular epidemiology of enterococcal isolates from patients with urinary tract infections in Shanghai, China - Weiyi Wu; Shuzhen Xiao; Lizhong Han; Qiong Wu (Microbiology Spectrum)
ABSTRACT Urinary tract infections (UTIs) are among the most prevalent infectious diseases, yet there is still limited understanding of the epidemiology of Enterococcal strains isolated from UTI patients in Shanghai. This study aims to elucidate the antimicrobial resistance profiles, virulence gene carriage, and molecular epidemiology of selected Enterococcal strains from UTI patients in Shanghai. A cohort of 80 Enterococcus faecalis and 40 Enterococcus faecium clinical isolates were randomly selected from UTI patients from October 2022 to March 2023. No vancomycin-resistant strains were identified based on minimum inhibitory concentration (MIC) testing. However, five strains of linezolid-resistant E. faecalis were identified, all of which were confirmed to be optrA-positive through whole-genome sequencing (WGS), with ST300 being reported as the first instance of this ST type in China. Polymerase chain reaction (PCR) assays were employed to ascertain the presence of virulence genes and multi-locus sequence type (MLST). In E. faecalis, the most common virulence genes were asal (75%), gelE (65%), esp (52.5%), and cylA (47.5%). In contrast, E. faecium primarily exhibited esp (65%) and hyl (12.5%). Among the E. faecalis strains, 21 distinct MLST types were identified, with ST16 and ST179 prevailing. Conversely, E. faecium exhibited only five MLST types, with ST78 being predominant. The prevalence of E. faecalis CC16 and E. faecium CC17 further complicates the treatment landscape for Enterococcal UTIs.IMPORTANCEThis study highlighted the critical need to understand Enterococcal strains causing UTIs in Shanghai, given their high prevalence. By assessing antimicrobial resistance profiles, virulence gene presence, and molecular epidemiology, the research offered valuable insights into the local epidemiology of Enterococcus faecalis and Enterococcus. faecium. Identifying linezolid-resistant strains, all of which carry the optrA gene, including the first report of ST300 in China and recognizing dominant MLST types, such as ST16 and ST179 for E. faecalis and ST78 for E. faecium, are vital for guiding treatment and addressing the challenges these infections present. The data emphasize the need for ongoing surveillance and customized therapeutic approaches to combat emerging resistance and virulence factors in Enterococcal UTIs.